ESTIMATES OF THE AVERAGE NUMBER OF TIMES STUDENTS SAY THEY CHEATED. - Liebler, Robert (College Student Journal)
Data from published studies is used to recover information about the sample mean self-reported number o f times cheated by college students. The sample means were estimated by fitting distributions to the reported data. The few estimated sample means thus recovered were roughly 2 or less.